Exercise training improves vascular function and secondary health measures in survivors of pediatric oncology related cerebral insult - Long, T.; Rath, S.; Wallman, K.; Howie, E.; Straker, Leon; Bullock, A.; Walwyn, T.; Gottardo, N.; Cole, C.; Choong, C.; Naylor, L. (Public Library of Science, 2018)
Adolescent and young adult (AYA) survivors of pediatric oncology related cerebral insult are vulnerable to numerous treatment-induced deficits that significantly enhance cardiovascular disease risk. Regular exercise improves endothelial function, fitness, body composition and musculoskeletal function which may reduce predisposition for cardiovascular disease. Here we assessed the feasibility and effectiveness of a 24-week exercise intervention on cardiovascular, physical and metabolic outcomes in this population. Thirteen survivors (6 male, 7 female; median age 19 y (range 16–23 y) were recruited to participate in a 48-week study consisting of a 24-week control period (regular care) followed by a 24-week exercise intervention. Outcome measures were collected at entry (week 0) and following regular care (24-week) and exercise (48-week). Assessed variables included endothelial function (flow mediated dilation, FMD), blood pressure, heart rate (HR), aerobic capacity, anthropometry, body composition, muscular strength (3 repetition maximum testing), muscular endurance (repetitions/min) and physical activity levels (accelerometry). Compared to baseline, delta diameter (p = 0.008) and FMD (p = 0.029) of the brachial artery increased following exercise. Bicep-curl strength also increased following exercise compared to baseline (p = 0.019), while submaximal (6 min mark) measures of ventilation (p = 0.012), rating of perceived exertion (p = 0.012), HR (p = 0.001), absolute (p = 0.000) and relative (p = 0.000) aerobic capacity decreased. Breaks in sedentary time increased (p = 0.043) following exercise compared to regular care. Although the sample was small and heterogeneous, this study demonstrates that exercise is achievable and has positive effects on vascular function, submaximal fitness, local strength and physical activity in a population of AYA survivors of pediatric oncology related cerebral insult.